2016
DOI: 10.1190/geo2015-0226.1
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven selection of the minimum-gradient support parameter in time-lapse focused electric imaging

Abstract: We have considered the problem of the choice of the minimum-gradient support (MGS) parameter in focused inversion for time-lapse (TL) electric resistivity tomography. Most existing approaches have relied either on an arbitrary choice of this parameter or one based on the prior information, such as the expected contrast in the TL image. We have decided to select the MGS parameter using a line search based on the value of the TL data root-mean-square misfit at the first iteration of the nonlinear inversion proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Many authors have observed poor recovery of mass‐balance in tracing experiments [e.g., Singha and Gorelick , ; Müller et al ., ] and over‐ or underestimation of the physical properties due to over‐smoothing of the geophysical image [e.g., Vanderborght et al ., ; Hermans et al ., ]. Some authors have proposed alternative constraints to the standard smoothness constraint in order to reduce smoothing and better estimate physical properties [ Doetsch et al ., ; Fiandaca et al ., ; Caterina et al ., ; Nguyen et al ., ; Hermans et al ., ], but the inherent limitations of deterministic inversion remain.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have observed poor recovery of mass‐balance in tracing experiments [e.g., Singha and Gorelick , ; Müller et al ., ] and over‐ or underestimation of the physical properties due to over‐smoothing of the geophysical image [e.g., Vanderborght et al ., ; Hermans et al ., ]. Some authors have proposed alternative constraints to the standard smoothness constraint in order to reduce smoothing and better estimate physical properties [ Doetsch et al ., ; Fiandaca et al ., ; Caterina et al ., ; Nguyen et al ., ; Hermans et al ., ], but the inherent limitations of deterministic inversion remain.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that regularization in a time-lapse mode is similar to a static mode, very few studies have investigated the use of alternative spatial regularization operators in time-lapse studies more adapted to the physics of the process (Ajo- Franklin et al, 2007;Doetsch et al, 2010;Fiandaca et al, 2015;Nguyen et al, 2016). Coupled hydrogeophysical inversion schemes are promising.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Fiandaca et al (2015) and Nguyen et al (2016) apply the MS and minimum gradient-support (MGS) functionals to time-lapse ERT inversion to produce focused time-lapse changes. This is of particular interest to image preferential flow paths in fractured aquifers or preferential infiltration processes.…”
Section: Introductionmentioning
confidence: 99%
“…However, surface measurements provided by P32 were found to have limited spatial resolution due to the presence of artifacts and a high amount of noise. At other industrial sites, a different approach such as time‐lapse inversion of ratio or focused time‐lapse inversion (Rosas Carbajal et al, 2012; Vignoli et al, 2015; Nguyen et al, 2016) might be considered, as they have proven to be successful in avoiding inversion artifacts.…”
Section: Discussionmentioning
confidence: 99%